Zinc-α2-Glycoprotein Is Associated with Obesity in Chinese People and HFD-Induced Obese Mice - Liu, Meijuan; Zhu, Huijuan; Dai, Yufei; Pan, Hui; Li, Naishi; Wang, Linjie; Yang, Hongbo; Yan, Kemin; Gong, Fengying (Frontiers in Physiology, 2018)
Zinc-α2-glycoprotein (ZAG) plays an important role in the regulation of body weight, body fat and glucose metabolism. In this study, we first measured ZAG levels in serum and ZAG mRNA levels in subcutaneous white adipose tissue (sWAT) among overweight/obese patients and lean control subjects. Second, we investigated the effects of ZAG administration on body weight, body fat and glucose metabolism of high-fat diet (HFD)-induced obese ICR mice and the possible mechanisms involved. The results showed that serum ZAG and mRNA levels in sWAT were significantly decreased in overweight/obese patients and that both showed a negative association with body mass index (BMI) and body weight after adjustment for age and sex. Further partial correlation analysis found that ZAG mRNA expression was positively related with several WAT browning-related genes, including uncoupling protein 1 (UCP1) (r=0.67) and peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC1a) (r=0.60), in the sWAT of all subjects. Additionally, intraperitoneal injection of a ZAG expression plasmid (5 μg/injection, four times a week) in HFD-induced obese mice for 8 weeks demonstrated that ZAG overexpression significantly decreased body weight and WAT mass, and greatly increased the glucose tolerance of obese mice, as shown by the intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin tolerance test (IPITT). The staining of UCP1-positive adipocytes was significantly stronger in the sWAT of ZAG-treated obese mice than that of obese control mice. The mRNA and protein levels of PGC1α in sWAT were significantly increased to 2.2-fold and 5.3-fold, respectively, compared with HFD obese mice, and there was a strong positive correlation between the expression levels of Zag and Pgc1α in mouse sWAT (r=0.74). A similar phenomenon was also observed in visceral white adipose tissue (vWAT): the mRNA and protein levels of PGC1α were increased to 1.9-fold and 3.6-fold, respectively, when obese mice were treated with ZAG. In conclusion, ZAG levels in both sWAT and serum are inversely related with BMI and body weight in Chinese subjects. The action of ZAG on body weight, fat mass and glucose metabolism may be realized through activating PGC1α expression in sWAT and vWAT, then promoting WAT browning in obese mice.